Comparing primary insomnia to the insomnia occurring in major depression and general anxiety disorder. (December 2019) - Sun, Qiaoling; Tan, Liwen
Highlights: Major depression with insomnia shows more active REM sleep than primary insomnia and general anxiety disorder. Primary insomnia and general anxiety disorder with insomnia have similar sleep architectures. From the view of sleep architectures, major depression with insomnia and primary insomnia may be categorically different. Abstract: Apart from possibly distinguishing the different clinical causes of insomnia, this article explores the subjective and objective sleep differences amongst primary insomnia, major depression with insomnia and general anxiety disorder with insomnia. Subjective sleep and objective sleep of the participants were evaluated by using the Pittsburgh sleep quality index and polysomnography, respectively. We found that major depression with insomnia exhibited higher daytime dysfunction than primary insomnia; showed significantly higher values of rapid eye movement (REM) periods, time of REM sleep and percentage of REM stage; and presented lower percentage of non-rapid eye movement stage compared with primary insomnia and general anxiety disorder with insomnia ( p < 0.05). General anxiety disorder with insomnia showed lower awakening number (AN) than primary insomnia, and other objective and subjective sleep values of general anxiety disorder with insomnia and primary insomnia showed no significant difference ( p > 0.05). Our findings showed that major depression with insomnia increased active REM sleep and severe daytime function, which could alert clinicians to the risk of depression. Major depression with insomnia and primary insomnia may be categorically different. However, general anxiety disorder with insomnia and primary insomnia might be a continuum of a disease rather than be categorically distinct.